MST Study Plan: a genealogical analysis in the curricular domain of Mathematics - Sachs, Línlya [UNESP]; Nogueira, Amanda Araújo Coelho; de Souza, Luiza Gabriela Razêra (FapUNIFESP (SciELO), 2023)
In 2013, the Education Sector of the Landless Workers’ Movement (MST) in the state of Paraná published the Study Plan for the final years of Elementary School. It is a curricular proposal aimed at rural schools in areas of agrarian reform in the state (itinerant schools, in camps, and schools in rural settlements). Based on Foucault’s genealogical tactics, the aim of this article is to problematize what is stated in the Study Plan on the curricular domain of Mathematics. In this sense, Foucault’s theorizations allow us to understand how the set of authorized knowledge, together with a bundle of relationships that establish it, organically deprives and undermines the forms of knowledge that do not pass through the sieve of scientific discourse. For this, the research was divided into two stages: (i) an analysis of the mathematical themes present in the Study Plan; and (ii) conducting interviews with people involved in the preparation of the Study Plan. The conclusion is that the relationship established, in the Study Plan, between the mathematical contents determined by official curriculum and the portions of reality, occurs in a naive and, sometimes, inconsistent way, (re)producing the truth of Mathematics. Also, the intricacies of its elaboration were evidenced, explaining conflicts and showing that the subject is an effect of the power-knowledge relations.
Plano de Estudos do MST: uma análise genealógica no domínio curricular da Matemática
Keywords: Curriculum; Genealogy; Landless Workers' Movement; Rural Education; Subject Knowledge